2017
DOI: 10.1253/circj.cj-16-0616
|View full text |Cite
|
Sign up to set email alerts
|

Shock Index More Sensitive Than Cardiogenic Shock in ST-Elevation Myocardial Infarction Treated by Primary Percutaneous Coronary Intervention

Abstract: a small cohort of patients. 9 Recently, Spyridopoulos et al showed that SI is an independent and stronger predictor of long-term mortality in older patients with STEMI. 10 In that study, however, an unusual definition of CS (SBP <100 mmHg with HR >100 beats/min) was used, which makes it difficult to compare the results with previous studies and to extrapolate it into daily practice. Furthermore, they did not assess the optimal cut-off for SI, but used a self-chosen cut-off, which was different from previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Three studies evaluated the influence of high SI on the prognosis in 14,759 STEMI patients. [ 7 , 9 , 11 ] Adverse outcomes (all-cause mortality or MACE) were significantly higher in the high SI group compared with the low SI group (pooled RR = 1.93, 95% CI: 1.10–3.39, P = .02; I 2 = 95%) (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Three studies evaluated the influence of high SI on the prognosis in 14,759 STEMI patients. [ 7 , 9 , 11 ] Adverse outcomes (all-cause mortality or MACE) were significantly higher in the high SI group compared with the low SI group (pooled RR = 1.93, 95% CI: 1.10–3.39, P = .02; I 2 = 95%) (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 98%
“…Of the 8 studies, 2 showed only in-hospital mortality, [ 6 , 13 ] 2 reported only short-term adverse outcomes, [ 7 , 9 ] 2 assessed only long-term MACE, [ 10 , 12 ] 1 evaluated both in-hospital and long-term mortality, [ 8 ] and 1 measured both short-term and long-term mortality. [ 11 ] Therefore, there were 3, 3, and 4 studies for the analyses of in-hospital mortality, short-term, and long-term adverse outcomes, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between SI and greater in-hospital mortality risk in patients with NSTEMI has also been confirmed 19 , and elevated SI also correlates with a poorer 5-year prognosis in patients with AMI undergoing PCI 20 . In most of these studies, SI values of<0.7 are considered normal 12 , 14 , 16 , 18 , 19 . We hypothesized that SI could predict long-term prognosis in ACS patients undergoing PCI and that it can identify those patients who are at high risk of adverse cardiac events.…”
Section: Introductionmentioning
confidence: 99%